(untitled) (Journal of the College of Basic Education, 2022)
In sum, we can consider (Romance in the Poetry of Abi Shadi) an important topic because it sheds light on the poet Ahmed Zaki, who is considered a pioneer of the romantic school, and he was at the head of the Apollo group with what he called for renewal, if he cared about the organic unity that makes the poem a coherent structure that rotates In one subject, the poet also relied on expressions that tend to sweetness, in addition to that.Sometimes he finds happiness and warmth in him, and sometimes he enjoys his misery.